A straightforward method to prepare supported Au clusters by mechanochemistry and its application in photocatalysis. (December 2020) - Chen, Yufen; Soler, Lluís; Xie, Chenyang; Vendrell, Xavier; Serafin, Jarosław; Crespo, Daniel; Llorca, Jordi
Highlights: Au clusters are produced by one-step ball milling from TiO2 and Au acetate. Mechanochemically synthesized Au/TiO2 exhibits superior photocatalytic activity. Ball milling results in efficient charge separation and photocurrent response. Ball milling can provide highly active metal-semiconductor photocatalysts. Abstract: Reducing the metal particle size on semiconductor-based materials from a few nanometers down to well-dispersed clusters or single atoms has been demonstrated to be an effective strategy to enhance the photocatalytic performance. However, designing a simple and fast synthesis procedure has consistently been a challenge. In this work, gold clusters have been easily synthesized and dispersed onto TiO2 surface by one-step ball milling from TiO2 and gold acetate. The Au clusters strongly interact with TiO2 and the resulting material exhibits outstanding photocatalytic performances on the generation of hydrogen under UV and visible light, which double those obtained on conventional Au/TiO2 photocatalysts containing Au nanoparticles. We have studied the effect of various preparation parameters and characterized the samples by a variety of microscopic and spectroscopic techniques. The particular architecture accomplished by ball milling results in efficient charge separation, low charge transfer resistance and high photocurrent response. This mechanochemical method not only provides a facile and cost-effective alternative to the conventional methods of fabricating Au/TiO2 catalysts, but also opens a promising avenue for developing other ultrasmall metal clusters onto different supports. Graphical abstract: Image, graphical abstract